Politics, governance and conflict management - Dhar, T.N. (2002)
The article attempts to identify and flag the causes and symptoms of social tensions that arise from the incompatible aspirations of communities, groups and societies. It focuses on the perils faced by national unity, harmony and integrity due to violent coercive attempts at resolving these issues. The author suggests possible ways and means by which political and administrative responses can be generated and administered to minimise conflicts and to ensure all-round progress in united, equitable and harmonious ways. - Reproduced.
Keywords: Politics and government; Public administration; Social conflicts; Conflict resolutions